Portretul Mariei (Lupu) Radziwill reflectat într-o lucrare a pictorului polonez Korneli Szlegiel (1851) / Portrait of Maria (Lupu) Radziwill in the works of the Polish painter Korneli Szlegiel (1851) - Lilia Zabolotnaia; Sorin Iftimi (Tyragetia, 2016)
This article is an attempt to critically review the visual documentation regarding the Vasile Lupu time that are of great interest for the Romanian and Polish historiography. We tried to compare some fragments from the life of Maria (Lupu) Radziwill with her preserved visual images. The groundwork of this scientific approach are illustrated sources of the epoch, in particular the frescoes in the Three Holy Hierarchs Church of Iaşi, which have been renovated during 1880s, and the portrait created by Szlegiel in 1851 that preserved the original images of the church frescoes before their renovation. Our study substantiates the authenticity and singularity of the Korneli Slegiel's portrait depicting the royal family of Vasile Lupu for the reason that it preserves the original appearance of the 17th century frescoes. Unknown drawing made by Korneli Szlegiel was discovered in the Warsaw National Mseum (Muzeum Narodowe w Warszawie) in 2015. The images were exposed to interdisciplinary research, being examined from a purely artistic perspective as well as a cultural and historical point of view. The data of this study might be the basis of a subsequent reliable restoration of frescoes of the Three Holy Hierarchs Church.